Peningkatan Kompetensi Guru melalui Pelatihan Media Pembelajaran Kreatif dan Inovatif Berbasis Problem Based Learning di MI Islamiyah Sumur Putih Pamekasan - Sri Harini; Yanti Linarsih; Royyan Julian; Sri Indriati Hasanah; Hasan Basri; Chairul Fajar Tafrilyanto; Naufalia Wardani Rahman; Asifaul Ulum; Syamsiyatul Maghfiroh (Universitas Madura, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PkM) aimed to enhance teachers’ pedagogical and professional competencies through training on the development of creative and innovative learning media based on Problem Based Learning (PBL) by utilizing GeoGebra at MI Islamiyah Sumur Putih, Pamekasan. The program was conducted in response to teachers’ needs for learning media that are not merely conventional, but capable of fostering active student engagement, critical thinking, and problem-solving skills in line with the demands of 21st-century learning. The implementation method employed a training and workshop approach consisting of needs analysis and observation, delivery of materials on PBL concepts and the use of GeoGebra as an interactive learning medium, hands-on practice in designing PBL-based learning media, presentation of the developed products, and joint reflection and evaluation. The results indicated an improvement in teachers’ understanding of PBL implementation as well as practical skills in designing and applying GeoGebra-based learning media that are creative, innovative, and contextual. The interactive and participatory nature of the activities also encouraged a shift in learning paradigms from teacher-centered to student-centered approaches. The program received positive responses from the partner school and is expected to have a sustainable impact on improving the quality of teaching and learning processes in the madrasah.